Babur - Prose Writer, Master Of Portrait And Landscape (Texas Journal of Philology, Culture and History, 2022)
This article discusses the problem of studying "Babur-name", the ideological and artistic features of the work, and also provides examples of the skill of Babur as a portrait and landscape painter.